The Effect of Advertising and Physical Evidence on Consumer Decisions in Using the Trans Metro Deli Bus in Medan City - Muhammad Fahmi; Liya Depriana (Journal of International Conference Proceedings (JICP), 2022)
The purpose of this study was to determine and analyze the effect of advertising and physical evidence on consumer decisions in using the Trans Metro Deli Bus in Medan City. The research method used in this research is using quantitative methods. The population in this study were the consumers of the Trans Metro Deli Bus in Medan City, while the research sample was 100 consumers who were selected by accidental sampling along the 5 routes traversed by the Deli Bus. The data collection technique in this study used the Questionnaire (Questionnaire) technique. The data analysis technique in this study uses Multiple Linear Regression, Classical Assumption Test, t-test and F-test, and the Coefficient of Determination. Management of data in this study using the SPSS 21 software program. Partially it is known that advertising has a significant influence on consumer decisions. Partially it is known that Physical Evidence has a significant influence on Consumer Decisions. Meanwhile, it is simultaneously known that advertising and physical evidence have a significant influence on consumer decisions to use the Trans Metro Deli Bus in Medan City.Keywords: Advertising, Physical Evidence, Consumer Decision